Impact of urban violence on workers in Family Health Strategies in risk areas (Research, Society and Development, 2020)
The objective was to reflect on the impact of urban violence on the experience of health professionals in the Family Health Strategy on the development of care in areas at risk. This is a study of critical reflection, with a qualitative, descriptive approach, anchored in the experience lived during the data collection of a transversal research carried out in the units of the Family Health Strategy, in the city of Rio de Janeiro, with 88 health professionals. The results point in these environments, health professionals who work in areas of risk, and feel afraid and try to react positively in the face of adversities in the development of health care. However, user service is impaired due to the high rates of urban violence, situations that include psychological, physical and social issues. It was concluded from the reflections made, that preventive measures of primary, secondary and tertiary order are necessary, with investments in the short, medium and long term, in addition to governmental, social, public policy and public health efforts, in order to minimize the problem of urban violence aimed at providing quality and safe assistance to users of the Family Health Strategy. This study seeks to contribute to nursing, the multidisciplinary team, public health and society as a whole.